The Development of Augmented Reality-based Geometry Module (AR-Geo) to Improve Spatial Ability in Learning 3D Geometry Material in SMA Negeri 3 Medan - Ardiningtyas, Mesayu; Azis, Zainal; Irvan, Irvan (Indonesian Journal of Education and Mathematical Science, 2024)
This research aims to develop an augmented reality-based teaching material, namely the AR-Geo module on 3D Geometry material at SMA Negeri 3 Medan. These teaching materials are able to determine the level of validity, practicality, and effectiveness of the AR-Geo module and student responses to learning. This research method used research and development (RD) through the ADDIE model. The subjects of the study involved students of class XII IPS 1 SMAN 3 Medan in the academic year 2023/2024 totaling 36 students. The research instruments employed AR-Geo module assessment sheets by media and material expert lecturers, mathematics teachers, peers, student ability tests and student response questionnaires, as well as student spatial ability tests. The results indicate that the material expert score is 91,53% and the design expert score is 90,53%, classified as very valid. The practicality of the module can be identified from the teacher response questionnaire score of 80,00% classified as practical, and the questionnaire score in the small group trial of 84,26%, field test 84,38% classified as very practical. The effectiveness is shown by 83,33% of students completing the learning outcomes test, and the results of the N-Gain calculation are 17 students experiencing an increase in medium spatial ability and 19 students experiencing an increase in high spatial ability. As a result, the development of augmented reality-based modules for 3D geometry material that has been developed is feasible to use.